2020
DOI: 10.1063/1674-0068/cjcp1907136
|View full text |Cite
|
Sign up to set email alerts
|

Tuning structural, electronic, and magnetic properties of black-AsP monolayer by adatom adsorptions: A first principles study

Abstract: Black Arsenic-phosphorus (AsP) monolayer is a novel two-dimensional nanomaterial with the characteristics of modest direct bandgap and superhigh carrier mobility. However, little is known about how the surface adsorption affects the property of AsP monolayer. Motivated by this, we researched systematically the geometry, adsorption energy, magnetic moment and electronic structure of 11 different adatoms adsorbed on AsP monolayer using first-principles calculations. The adatoms used in this study include light n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Further, the adsorption of some atoms can induce relatively large magnetic properties in the AsP monolayer. For example, AsP decorated with N, Ti, and Fe becomes a bipolar semiconductor, while AsP decorated with Mn becomes a bipolar spin-gap semiconductor [70]. Ozdemir et al examined the effect of adsorbed atoms on the structural, electronic, and magnetic properties of the β-AsP and α-AsP phases.…”
Section: Doping Regulationmentioning
confidence: 99%
“…Further, the adsorption of some atoms can induce relatively large magnetic properties in the AsP monolayer. For example, AsP decorated with N, Ti, and Fe becomes a bipolar semiconductor, while AsP decorated with Mn becomes a bipolar spin-gap semiconductor [70]. Ozdemir et al examined the effect of adsorbed atoms on the structural, electronic, and magnetic properties of the β-AsP and α-AsP phases.…”
Section: Doping Regulationmentioning
confidence: 99%
“…Graphene, TMDs, and group VA binary materials with tunable properties can be synthesized through such alloying or doping methods [38][39][40]. In the past several years, it has been shown that arsenic can be incorporated into black phosphorus via a high-pressure process, and these materials show excellent physical and chemical properties [41,42]. Moreover, for the synthesis of group VA binary materials with different and adjustable mole fractions, various methods have been introduced, such as the novel mineralizer-assisted short way chemical transport reaction, vapor transport method, and molecular beam epitaxy [24,40].…”
Section: Introductionmentioning
confidence: 99%